The overheating effects in germanium quantum well with two subbands occupied - Berkutov, I.B.; Andrievskii, V.V.; Kolesnichenko, Yu.A.; Komnik, Yu.F.; Mironov, O.A. (Физика низких температур, 2018)
The charge carrier overheating effect was studied in the p-type Si₀.₄Ge₀.₆/Ge/Si₀.₄Ge₀.₆ heterostructure with two subband occupy. The temperature dependences of hole-phonon relaxation time τh-ph at weak magnetic fields demonstrated transition of the 2D system from regime of “partial inelasticity” characterized by dependence τ⁻¹h-ph ∝ T² to regime of small-angle scattering, described by dependence τ-1h-ph ∝ T⁵ with temperature increase. But in higher magnetic fields the dependence τ⁻¹h-ph ∝ T³ manifests itself on dependences τh-ph(Th-ph). The possible explanations of such dependences are discussed. Ефект перегріву носіїв заряду вивчався в гетероструктурі Si₀.₄Ge₀.₆/Ge/Si₀.₄Ge₀.₆ p-типу з двома зайнятими підзонами. В слабких магнітних полях температурні залежності часу дірково-фононної релаксації h-ph τ демонструють перехід двовимірної системи з режиму «часткової непружності», яка характеризується залежністю τ⁻¹h-ph ∝ T² до режиму малокутового розсіювання, що описується залежністю τ-1h-ph ∝ T⁵ з підвищенням температури. В більш високих магнітних полях залежність τ⁻¹h-ph ∝ T³ змінюється на -ph -ph ( ) τh hT . Обговорюються можливі варіанти пояснення таких спостережень.